Effect of Juice Berry Fruit (Antidesma bunius (L.) Spreng.) on Total Cholesterol Levels in Mice (Mus musculus Linnaeus, 1758) with Hypercholesterolemia: Pemberian Jus Buah Buni (Antidesma bunius (L.) Spreng) terhadap Kadar Kolesterol Total pada Mencit Jantan (Mus musculus Linnaeus, 1758) Hiperkolesterolemia - Isnaini, Nurul; Nurcahyani, Nuning; Fithria Mumtazah, Dzul; Sutyarso (Department of Biology Faculty of Mathematics and Natural Sciences Universitas Lampung in collaboration with The Indonesian Association of Biology (PBI) Lampung Branch., 2025)
Hypercholesterolemia is influenced by excessive fat consumption. To lower blood cholesterol levels, both drug and non-drug therapy can be carried out. One plant that has the potential to lower cholesterol levels is the buni plant (Antidesma bunius (L.) Spreng.). This study aims to determine the effect of buni fruit juice and the most effective juice concentration in lowering total cholesterol levels in hypercholesterolemic male mice. This study used a completely randomized design consisting of 5 groups, each repeated 5 times. The experimental animals were given a High Fat Diet (MDTL) containing propylthiouracil (PTU) at a dose of 1.8 mg/200g BW suspended in 2% Pure Grain Alcohol (PGA) and 10 mL/KgBW of quail egg yolk. The treatments consisted of a negative control (standard feed); a positive control (MDTL and 0.52 mg simvastatin); P1 (MDTL and 1 ml of 20% buni fruit juice); P2 (MDTL and 1 ml of 25% berry juice); and P3 (MDTL and 1 ml of 30% berry juice). Treatments P1, P2, and P3 were administered MDTL for 14 days, followed by berry juice for another 14 days. The results were total blood cholesterol levels. Data were analyzed using a one-way ANOVA followed by Duncan's test at a confidence level of α = 5%. The results showed that administration of 30% berry juice reduced total cholesterol levels in male mice with hypercholesterolemia.